Pelatihan Dasar Penggunaan Kecerdasan Buatan Generative AI Pada Kelompok Siswa Sekolah Menengah Atas - Miswanto Miswanto; Ndaru Ruseno; Toni Ali; Sigit Kurniawan (Politeknik Penerbangan Indonesia Curug, 2026)
The rapid development of information technology has brought changes to various industries, especially in the field of education. Artificial intelligence-based learning models, especially those that use web tools, have proven to be easier for students to understand and use, especially when the material is technical in nature. Currently, challenges arise when web applications that utilize Artificial Intelligence (AI) technology emerge, but we do not yet understand the basics of AI use itself. This community service activity aims to broaden students' knowledge of the use of Artificial Intelligence or AI-based applications so that they can be used more optimally to assist high school students in their teaching and learning activities. With this approach, a comprehensive understanding of the concept of Artificial Intelligence/AI can be achieved in a practical manner, thereby helping students find learning materials and tools that can be used to support activities both inside and outside of school. The target of this community service program is for the UTM Jakarta team to provide the basics of using “prompts” or commands that can help students find specific solutions in utilizing AI web application technology.